THE EFFECT OF VISUAL SCAFFOLDING STRATEGY TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE FIFTH GRADE OF SDN 087981 SIBOLGA - Tri Wahyuni; Irwandi; Widya Syafitri; Genta Sakti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigated the impact of Visual Scaffolding Strategy on vocabulary mastery among fifth grade students at SDN 087981 Sibolga. Utilizing a pre-experimental design, the study involved 21 students who participated in six sessions, including a pre-test, four treatment sessions, and a post-test. The findings revealed a significant improvement in vocabulary scores, with the mean score increasing from 54.76 on the pre-test to 85.75 on the post-test, resulting in an increase of 30.99. Statistical analysis confirmed that the t-test value (32.1) exceeded the critical t-table value (8.40), indicating that Visual Scaffolding Strategy effectively improved vocabulary mastery in this educational context. Consequently, the null hypothesis was rejected, confirming the positive effect of the strategy on students' learning outcomes.